Determining the Factors Influencing Job Satisfaction of Management and Professional Employees in Public Sector Malaysia - Zumrah, Abdul Rahim; Ali, Kalsom; Mokhtar, Ahmad Najaa’ (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
There are five work environment factors that influence job satisfaction of management and professional employees in this context. The factors include work stress, perceived organisational support, training, peer support, and participative leadership style. This study offers empirical support for the idea that job satisfaction plays a role in lowering turnover intentions, particularly among managerial and professional workers in Malaysia's public sector.